Penyuluhan Kesehatan Reproduksi Pada Remaja Putri - Gangsar Indah Lestari; Firda Fibrila; M Ridwan (CV. Multi Kreasi Media, 2023)
Adolescence is a transitional period, often individuals face confusing situations. This causes conflict in adolescents where many behaviors are strange, awkward, and if not controlled will cause delinquency in adolescents, one of which is the risk of risky sexual behavior. Some factors related to adolescent reproductive health include socioeconomic factors, cultural and environmental factors, psychological factors and biological factors. The influence of global information (exposure to audio-visual media) that is increasingly accessible and actually provokes adolescents to adapt unhealthy habits, which will accelerate the age of early sexual activity and lead them to high-risk sexual behavior, because most adolescents do not have accurate knowledge about reproductive health and sexuality and do not have access to reproductive health information and services, including contraception. One of the efforts that can be done is to conduct health education on how to care for reproductive organs, education about adolescent development during puberty, the impact of pornography, the impact of unwanted pregnancy, abortion, sexually transmitted diseases including HIV / AIDs and maturation of marriage age.